The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1088/1751-8113/41/43/435003
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic coarsening in voter models with intermediate states

Abstract: The introduction of intermediate states in the dynamics of the voter model modifies the ordering process and restores an effective surface tension. The logarithmic coarsening of the conventional voter model in two dimensions is eliminated in favour of an algebraic decay of the density of interfaces with time, compatible with Model A dynamics at low temperatures. This phenomenon is addressed by deriving Langevin equations for the dynamics of appropriately defined continuous fields. These equations are analyzed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 46 publications
10
38
0
Order By: Relevance
“…Such models with intermediate states have only recently begun receiving attention 30,31 in statistical physics literature, and we believe that this study is an important contribution to this body of literature.…”
Section: Introductionmentioning
confidence: 88%
“…Such models with intermediate states have only recently begun receiving attention 30,31 in statistical physics literature, and we believe that this study is an important contribution to this body of literature.…”
Section: Introductionmentioning
confidence: 88%
“…To illustrate our previous results, we now analyze a general class of 3-state models [13,14], known to exhibit curvature driven by surface tension, as recently shown in [15]. They are composed by two external absorbing states S = ±1, and an intermediate state S = 0.…”
mentioning
confidence: 84%
“…Interesting dynamical behaviors arise depending on the specific updating rules, the number of states and the functional form of the transition probabilities between configurations. For instance, it has been found that the addition of memory or inertia in the spin dynamics [11,12], the introduction of intermediate states [13][14][15], or the use of non-linear transitions [16], result in a drastic change of the coarsening properties and final outcome of the system.Despite that the dynamical rules of the models are very different in nature, many of them seem to share the same macroscopic behavior, such as coarsening and criticality. However, the minimal conditions that a microscopic dynamics must hold in order to observe a particular behavior have not been clearly identified yet.…”
mentioning
confidence: 99%
See 2 more Smart Citations